2022
DOI: 10.1109/access.2022.3228496
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Precoding for mmWave MIMO Systems With Overlapped Subarray Architecture

Abstract: Traditional precoding is incompatible with millimetre wave (mmWave) multiple input multiple output (MIMO) systems due to hardware costs and power consumption. As a result, hybrid precoding is being considered as a promising technology for balancing hardware complexity and system performance. This paper proposes a hybrid precoding technique for overlapped subarrays (OSA) architecture in mmWave MIMO systems. It exploits the OSA's structure to decompose the hybrid precoding problem into a series of 𝐿 𝑡 𝑁 𝑠 /2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 29 publications
(83 reference statements)
0
16
0
Order By: Relevance
“…Recently, several low complexity algorithms for hybrid precoding and combining in 5G mmWave massive MIMO systems have been proposed and studied [33][34][35]. In [33], researchers proposed a hybrid precoding/combining algorithm based on the simultaneous orthogonal matching pursuit technique and demonstrated comparable performance to an optimal digital beamformer.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several low complexity algorithms for hybrid precoding and combining in 5G mmWave massive MIMO systems have been proposed and studied [33][34][35]. In [33], researchers proposed a hybrid precoding/combining algorithm based on the simultaneous orthogonal matching pursuit technique and demonstrated comparable performance to an optimal digital beamformer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, ref. [35] proposed using an iterative hybrid precoding for overlapped subarray architecture to improve the spectral efficiency of the subarray architecture. The work in [35] showed that using an overlapped subarray architecture can improve spectral efficiency while still lower than the full array architectures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, there are two types of hybrid precoding and combining techniques: full array [7], [8] and subarray [21]- [23]. In the full array structure, every RF chain is linked to all the antenna elements, whereas in the subarray arrangement, each RF chain is connected to a portion of the antenna elements.…”
Section: Digitalmentioning
confidence: 99%
“…Recently, SA architectures have received a lot of attention because of their reduced complexity. SA architectures can be categorized into fixed SA [8], [15]- [22] and dynamic SA (DSA) [23]- [7], [27]. A closed-form solution for fully connected hybrid precoding based on OFDM is derived in [7] for mmWave systems.…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that linear zero-forcing was utilized at the digital baseband, the complicated hybrid precoder optimization problem was reduced to an eigenvalue maximization problem. To increase the spectral efficiency of the SA design, the authors of [22] proposed an overlapping SA architecture with iterative hybrid precoding. The results showed that the overlapped SA architecture, while slightly more complex in terms of hardware than the fixed SA architecture, can improve spectral efficiency while still being less complex than the DSA and FA structures.…”
Section: Introductionmentioning
confidence: 99%